Some Structural Differences in the Wood of Boswellla serrata Roxb., Garuga pinnata Roxb, Lannea coromandelica Merr. And Spondias pinnata Kurz - Chauhan, Laxmi; Dayal, R. (Indian Forester, 1990)
Anatomical studles carried out on Boswellia serrata Roxb, Garuga pinnata Roxb., Lannea coromandelica Merr. and Spondias pinnata Knrz. with a view to ascertaining the diagnostic value of radial gum canals and cell inclusions indicate that features like size and frequency of gum canals, nature of epithelial cells and cell inclusions i e, occurrence of crystals and silica are likely to be of diagnostic value in identification of woods of these species.